PIEZOELECTRIC EFFECT AND ITS APPLICATIONS IN MODERN TECHNOLOGIES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the piezoelectric effect and its applications in modern technologies. The piezoelectric effect, discovered in 1880 by the Curie brothers, is the ability of certain crystalline materials to generate electrical charge in response to mechanical stress and vice versa. The study explores the fundamental principles of piezoelectricity, analyzes its theoretical foundations, and investigates experimental methods for studying this phenomenon. The article reviews the wide range of modern applications including sensors, actuators, energy harvesting devices, medical equipment, and consumer electronics. Special attention is given to recent innovations in flexible piezoelectric materials, nanostructured devices, and sustainable energy applications. The research demonstrates the growing importance of piezoelectric technologies in advancing smart materials, Internet of Things (IoT) devices, and renewable energy systems.